1993
DOI: 10.1017/s0022149x00012840
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the morphology of adults and larval stages of Oesophagostomum sp. isolated from man in northern Togo and Ghana

Abstract: Infection with Oesophagostomum sp. appears to be extremely common in man in northern Togo and Ghana Adult specimens were recovered from the intestinal lumen by treatment with pyrantel pamoate and the morphological characteristics of oesophagostomes of man could for the first time be compared with information available on the morphology of oesophagostomes of monkeys. The observations and measurements demonstrated that the species involved is Oesophagostomum bifurcum and that the eggs of this species cannot be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 15 publications
2
49
0
Order By: Relevance
“…Another explanation for the non-detection of hookworm positives with PCR might be that the hookworm eggs detected with the Kato–Katz and FLOTAC methods were from A. duodenale , a hookworm species that would not have been identified with the N. americanus -specific primers that we used in our PCR. Only the third-stage larvae of these helminths but not the morphological identical eggs allow a microscopic differentiation between A. duodenale and N. americanus 54. Studies that have undertaken differential diagnosis using coproculture in East Africa have shown that both A. duodenale and N. americanus do occur in East Africa but that the latter is the predominant species in the region 55–57…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for the non-detection of hookworm positives with PCR might be that the hookworm eggs detected with the Kato–Katz and FLOTAC methods were from A. duodenale , a hookworm species that would not have been identified with the N. americanus -specific primers that we used in our PCR. Only the third-stage larvae of these helminths but not the morphological identical eggs allow a microscopic differentiation between A. duodenale and N. americanus 54. Studies that have undertaken differential diagnosis using coproculture in East Africa have shown that both A. duodenale and N. americanus do occur in East Africa but that the latter is the predominant species in the region 55–57…”
Section: Discussionmentioning
confidence: 99%
“…recorded to date from non-human primates, O. bifurcum, O. stephanostomum, and O. aculeatum have also been reported in humans (Chabaud & Lariviere, 1958;Polderman & Blotkamp, 1995). Zoonosis caused by O. bifurcum is endemic in the northernmost part of Ghana and Togo situated in western Africa, and high prevalences of the disease in human residents have been recorded (Blotkamp et al, 1993;Polderman & Blotkamp, 1995;Pit et al, 1999;Yelifari et al, 2005;Gasser et al, 2006). Recently, however, multifaceted genetic analyses have demonstrated that different genotypes of O. bifurcum are prevalent in human patients and local non-human primates (Mona monkeys, Patas monkeys, Green monkeys, and Olive baboons) in Ghana and Togo (de Gruijter et al, 2004(de Gruijter et al, , 2005; reviewed by Gasser et al, 2006Gasser et al, , 2009, supporting parallel assump-HELMINTHOLOGIA, 51, 2: 83 -93, 2014 Prevalence and genetic diversity of Oesophagostomum stephanostomum in wild lowland gorillas at Moukalaba-Doudou National Park, Gabon tions based on epidemiological and morphological analyses de Gruijter et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…The taxonomy of the species important for human disease was studied by Chabaud and Lariviere and by Blotkamp, who recognized Oesophagostomum bifurcum as the most prevalent parasite in humans [4,5]. Although the disease is most often found in West Africa, sporadic cases have been described in other parts of Africa, Asia and South America [1,6,11,13,15].…”
Section: Introductionmentioning
confidence: 99%